Integrasi Perplexity AI pada Penulisan Teks Persuasi Dalam Bentuk Poster untuk Meningkatkan Kualitas Promosi Destinasi Wisata - Anshari; Sakaria; Asis Nojeng; Bahly Basri (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Gowa Regency has abundant natural and cultural tourism potential but faces challenges in delivering effective and attractive destination promotion to tourists. This community service activity (PKM) aims to improve the quality of tourism destination promotion in Gowa Regency and enhance the digital competence of partners through the integration of Perplexity.ai in persuasive text writing in poster form. The method used is a training held on October 2-3, 2025. The training participants were 36 students from SMA Negeri 9 Gowa, selected based on their interest in digital literacy, tourism promotion, and technology. The success of this activity was measured through several key indicators, including the participants' increased skills in utilizing Perplexity.ai for writing persuasive texts and creativity in poster design that meets tourism promotion standards. The analysis results show that integrating Perplexity.ai in persuasive text writing for tourism destination promotional posters successfully improved participants' skills significantly, with the average score increasing from 68 to 87. As many as 91% of participants were able to create effective and creative posters that received positive responses on social media and experienced an increase in digital literacy, making this training effective in developing participants' technical skills, creativity, and analytical abilities based on technology.